Multi-Scale Atmospheric Emissions, Circulation and Meteorological Drivers of Ozone Episodes in El Paso-Juárez Airshed - Nakul N. Karle; Rosa M. Fitzgerald; Ricardo K. Sakai; David W. Sullivan; William R. Stockwell (Atmosphere, 2021)
Ozone pollution has been prevalent in the El Paso-Juárez Airshed (EPJA), especially in the past few decades, and it has been on the rise recently. The spatial and temporal distribution of the tropospheric ozone and several key meteorological factors that influence its concentration has not been adequately understood. Therefore, this investigation comprehensively examined 57 high and 48 low ozone episodes occurring in this region during 2013–2019. We found that the interannual ozone concentration in EPJA was strongly affected by anthropogenic emissions. On the other hand, seasonal ozone variations are due to meteorological variables (among them, solar radiation, planetary boundary layer, and winds) in addition to biogenic emission factors. High ozone events are characterized by calm winds, shallow planetary boundary layer (PBL), whereas low ozone events were marked with strong winds, precipitation, and deep PBL. Synoptic and mesoscale wind patterns for these ozone episodes were identified and characterized. Most of the high ozone episodes occurred when an anticyclonic circulation aloft was associated with a 500-mile middle and upper tropospheric high-pressure region over the EPJA. During these events, stable air masses with convective available potential energies (CAPE) values of less than 450 J/kg were found. The importance of surface topography is illustrated by the fact that stations close to the Rio Grande River show a bimodal distribution of wind direction according to the valley axis. High ozone episodes occur with a surface easterly wind that is decoupled from winds above the Franklin mountains.